Massive attack of honeybee on macaws (Ara ararauna and Ara chloropterus) in Brazil – A case report - Milbradt, Elisane Lenita [UNESP]; Silva, Tarcísio Macedo [UNESP]; Hataka, Alessandre [UNESP]; Teixeira, Carlos Roberto [UNESP]; Okamoto, Adriano Sakai [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Elsevier, 2017)
Three adult birds of the species Ara chloropterus and five of the species Ara ararauna from a conservation breeding facility suffered a massive attack by honeybees. The A. chloropterus birds presented swollen puncture lesions with stingers (mainly in the facial regions without feathers), swelling of the eyelids and subcutaneous tissue, and respiratory distress, and they were treated with intramuscular injections of 1.67 mg/kg of promethazine and 10 mg/kg of hydrocortisone followed by removal of the stingers. Complete remission of the clinical signs occurred 48 hours after start of treatment. The five A. ararauna birds died before they arrived at the veterinary hospital, and the necropsies found stingers in the areas of the face without feathers and the subcutaneous tissue, which were associated with erythema, bruising, and swelling. Food content from the crop was found in the oral cavity and the tracheal lumen, and marked congestion was observed in the heart, liver, spleen, lungs, kidneys, brain, and cerebellum. Among the histopathological findings, significant swelling of the myocytes in the endocardium and vascular dilation with erythroid repletion were observed, and there were multifocal areas of centrilobular necrosis associated with severe congestion and hemorrhaging in the hepatic tissue. Severe acute tubular necrosis and hydropic-vacuolar degeneration were observed in the kidneys. The clinical signs and pathological findings suggest envenomation due to a massive bee attack, the first such report for Psittacidae.
Keywords: Avian pathology; Envenomation; Histopathology; Honeybee; Lesions; Macaw